Advancing Msmes Through Global Integration and Cross-Border Connectivity: Opportunities for Qris-Based Payment Code Development - Dona Putri Metri (PT Publikasiku Academic Solution, 2024)
Indonesia's rapid economic development in the digital era has witnessed a significant shift from traditional cash-based public payments to digital systems. Digital payments offer enhanced convenience, efficiency, security, and user-friendliness. Among these digital payment methods, QR Codes have emerged as a crucial solution, particularly during the COVID-19 pandemic, which led to a slump in the Indonesian economy due to social distancing measures. The adoption of the Quick Response Indonesian Standard (QRIS) as a cashless payment method by most Micro, Small, and Medium Enterprises (MSMEs) in Indonesia presents a promising solution due to its numerous advantages, including instant payment, enhanced security, easy setup, high reliability, and absence of associated charges. However, QRIS payments face limitations as they are inaccessible to foreigners without bank accounts or connections to Indonesian payment operators. To address this challenge, the Indonesian government has collaborated with four ASEAN countries to integrate the QRIS system with their respective user bases. Nevertheless, the global utilization of QRIS remains a problem that this study aims to address. One approach to promoting cross-border QR payment cooperation is to bolster the economic progress of MSMEs in each country. The objective of this study is to highlight the significant opportunities for developing integrated connectivity and cross-border QR payment codes in Indonesia. Further research is necessary to advance the development of prototypes, designs, and the implementation of integrated connectivity and cross-border QR payment code linkage on a global scale.